2003
DOI: 10.1136/mp.56.4.191
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of BRCA1 alternative splicing

Abstract: Germline mutations of the BRCA1 gene predispose individuals mainly to the development of breast and/or ovarian cancer. However, the exact function of the gene is still unclear, although the encoded proteins are involved in various cellular processes, including transcriptional regulation and DNA repair pathways. Several BRCA1 splice variants are found in different tissues, but in spite of intense investigations, their regulation and possible functions are poorly understood at the moment. This review summarises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 77 publications
2
113
0
1
Order By: Relevance
“…14 Alterations in the splicing pattern or splicing efficiency of several genes have been implicated in tumor progression (e.g., CD44, WT-1 and C-CAM1) and susceptibility to cancer (e.g., BRCA1). [15][16][17][18] In this study, we show a higher level of expression of the PIBF protein in breast tumors relative to normal breast tissue by immunohistochemistry. The TMA analysis suggested that at least 40% of breast tumors express a higher then normal level of PIBF.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…14 Alterations in the splicing pattern or splicing efficiency of several genes have been implicated in tumor progression (e.g., CD44, WT-1 and C-CAM1) and susceptibility to cancer (e.g., BRCA1). [15][16][17][18] In this study, we show a higher level of expression of the PIBF protein in breast tumors relative to normal breast tissue by immunohistochemistry. The TMA analysis suggested that at least 40% of breast tumors express a higher then normal level of PIBF.…”
Section: Discussionmentioning
confidence: 84%
“…17,18 One of the BRCA1 variants, deltaExon 11 missing two predicted nuclear localization signals was found to be localized in the cytoplasm, while the full-length protein was associated with the centrosome during mitosis and with the nucleus during interphase. 34,35 This is comparable to the predominant 35 kDa variant of PIBF that is also localized in the cytoplasm when it is overexpressed in HEK 293 cells and lacks the two predicted nuclear localization signals.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we show a marked accumulation of AML1 transcripts including a high frequency of a novel alternatively spliced AML1b transcript lacking exon 6 (AML1b Del179À242 ) in serous epithelial ovarian cancers suggesting that it may play an important role in ovarian tumorigenesis. Other proteins have been well documented to undergo alternative/aberrant splicing during cancer progression including mdm2 and BRCA1 (Bartel et al, 2002;Orban and Olah, 2003). Thus, deregulated splicing of oncogenes and tumor suppressors may be a common event during ovarian cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that BRCA mutation made a major contribution to the improved results. Individuals with BRCA mutation are at an increased risk of developing breast, ovarian, and other cancers [34]. More than 1 million women develop breast or ovarian cancer every year worldwide, and about 10% of them have a BRCA mutation [35][36][37], moreover that cancer patients with BRCA mutation have better outcomes than non-BRCA carriers [38,39].…”
Section: Discussionmentioning
confidence: 99%